2013
DOI: 10.1177/0044118x13490764
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects Between Exposure to Sexually Explicit Online Materials and Individual, Family, and Extrafamilial Factors on Hong Kong High School Students’ Beliefs About Gender Role Equality and Body-Centered Sexuality

Abstract: This study examined the interaction effects between Hong Kong adolescents' exposure to sexually explicit online materials (SEOM) and individual, family, peer, and cultural factors on their beliefs about gender role equality and body-centered sexuality. Based on a survey design with a sample of 503 high school students in Hong Kong, the results indicated that adolescents' frequency of accessing SEOM, their intrapersonal reactions to SEOM, their communication with parents about sexuality, their susceptibility to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…A third cross-sectional study found that the association between the use of Internet pornography and general beliefs about gender equality became more negative as adolescents talked more often about sex with their parents. However, a direct association between pornography use and gender equality was not present in that study (To et al, 2015). Similarly, a third longitudinal study did not find an association between how often adolescents used Internet pornography and genderstereotypical sexual beliefs (Peter & Valkenburg, 2011b).…”
Section: Sexual Attitudesmentioning
confidence: 66%
See 4 more Smart Citations
“…A third cross-sectional study found that the association between the use of Internet pornography and general beliefs about gender equality became more negative as adolescents talked more often about sex with their parents. However, a direct association between pornography use and gender equality was not present in that study (To et al, 2015). Similarly, a third longitudinal study did not find an association between how often adolescents used Internet pornography and genderstereotypical sexual beliefs (Peter & Valkenburg, 2011b).…”
Section: Sexual Attitudesmentioning
confidence: 66%
“…We therefore also included a quantitative study by Lo, Neilan, Sun, and Chiang (1999;cited in Lo and Wei 2005) and a quantitative study by Vandenbosch and Eggermont (2013b;cited in Vanden Abeele, Campbell, Eggermont, and Roe, 2014). In total, we thus reviewed 75 studies, 66 quantitative (see Appendix in Supplementary online data) and nine qualitative PETER AND VALKENBURG (2012) and To, Iu Kan, and Ngai (2015) relied on the same sample of adolescents in Hong Kong. Finally, the studies by and by Doornwaard, Bickham, Rich, ter Bogt, and van den Eijnden (2015) relied on one sample of Dutch adolescents.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations